Role of p73 Dinucleotide Polymorphism in Prostate Cancer and p73 Protein Isoform Balance. (6th July 2014) - Carastro, L. Michael; Lin, Hui-Yi; Park, Hyun Y.; Kim, Donghwa; Radlein, Selina; Hampton, Kaia K.; Hakam, Ardeshir; Zachariah, Babu; Pow-Sang, Julio; Park, Jong Y.
Abstract : Background . Molecular markers for prostate cancer (PCa) risks are currently lacking. Here we address the potential association of a dinucleotide polymorphism (DNP) in exon 2 of the p73 gene with PCa risk/progression and discern any disruption of p73 protein isoforms levels in cells harboring a p73 DNP allele. Methods . We investigated the association between p73 DNP genotype and PCa risk/aggressiveness and survival by fitting logistic regression models in 1, 292 incident cases and 682 controls. Results . Although we detected no association between p73 DNP and PCa risk, a significant inverse relationship between p73 DNP and PCa aggressiveness (AT/AT + GC/AT versus GC/GC, OR = 0.55, 95%Cl = 0.31–0.99) was detected. Also, p73 DNP is marginally associated with overall death (dominant model, HR = 0.76, 95%Cl = 0.57–1.00, P = 0.053 ) as well as PCa specific death (HR = 0.69, 95%Cl = 0.45–1.06, P = 0.09 ). Western blot analyses for p73 protein isoforms indicate that cells heterozygous for the p73 DNP have lower levels of ∆Np73 relative to TAp73 (P < 0.001 ). Conclusions . Our findings are consistent with an association between p73 DNP and low risk for PCa aggressiveness by increasing the expressed TAp73/∆Np73 protein isoform ratio.